Reimagining a pedagogy of care using ePortfolios as a scholarly, ‘visibility’ tool in higher education - Fisher, Marie; Penny, Wheeler (Journal of University Teaching and Learning Practice, 2025)
Assigning ePortfolio tasks to students should not only focus on instruction and activities that connect to real world learning. Humanising the learning experience by constructing an environment and teaching approach that builds trust, respect and resilience will strengthen learning partnerships, resulting in enhanced achievement for students (Henriksen et al., 2022). The aim of this paper is to consider how embodying a pedagogy of care can humanise the learning experience of ePortfolio activities in an online environment. How could we institute a pedagogy of care when designing ePortfolio tasks with academic colleagues? What strategies do we use to develop a safe space to reflect on our experience? How would a pedagogy of care approach improve student outcomes and inform new ways of working and studying? Findings indicated that implementation of the Modelling and Dialogue phases to support student learning, based on Noddings’ 1988 framework, enabled the students to transform their learning due to scaffolding, building trust and the authors encouraging a collegial environment to share feedback.